Mixed‐mode open tubular column for peptide separations by capillary electrochromatography. Issue 13 (31st May 2021) - Ali, Faiz; AlOthman, Zeid A.; Al‐Shaalan, Nora Hamad
Abstract: Mixed‐mode chromatography open tubular column has been developed for peptide separation in electrochromatography. A column with 92 cm effective length and 50 μm internal diameter is fabricated internally with a copolymer sheet of restricted thickness. Catalyst facilitated binding of the coupling agent 3, 5‐bis (trifluoromethyl) phenyl isocyanate has been carried out at the interior surface of the column. The initiator sodium diethyldithiocarbamate was bound to the coupling agent. A small amount of N ‐[2‐(acryloylamino) phenyl] acrylamide was used along with methacrylic acid and styrene in the monomer mixture to induce a little polar character in the stationary phase fabricated inside the column. Twenty‐three peptides have been separated from a chemically digested protein mixture present in cytochrome C in capillary electrochromatography, in addition to the separation of six commercial peptides. We achieved an average plate count of over 1.5 million/m with the column of current study both for the digested protein components and commercial peptides using 70/30% v/v (acetonitrile/20 mM ammonium formate) at pH 6.5. In addition, the column resulted in baseline separation of all the peptides with very good resolution, enhanced peak capacity, and better retention time span.